Virgin coconut oil prevents blood pressure elevation and improves endothelial functions in rats fed with repeatedly heated palm oil - Nurul Iman Badlishah Sham; Kamisah Y.; Jaarin K.; Qodriyah H.M.S. (2024)
Indexed by WOS/ Scopus